Analisis Filogenetik Molekuler pada Phyllanthus niruri L. (Euphorbiaceae) Menggunakan Urutan Basa DNA Daerah Internal Transcribed Spacer (ITS) - Topik Hidayat; Diah Kusumawaty; Kusdianti Kusdianti; Dian Din Yati; Astry Agusthina Muchtar; Dina Mariana (Institut Teknologi Bandung, 2008)
Variation of DNA sequences of the internal transcribed spacer (ITS) region has been used as a molecular character tounderstand the phylogenetic relationships within different strains of Phyllanthus niruri and with other species belonging tofamily Euphorbiaceae. Phylogenetic analysis of 19 plant samples using parsimony method revealed several findings: as awhole family, Euphorbiaceae is a monophyletic group and the family is divided into two major clades based upon its singleleaf arrangement; genus Phyllanthus is a non-monophyletic group, though species Phyllanthus niruri is a monophyleticgroup; major classification system of Phyllanthus niruri at the molecular level does not support previous majorclassification; Saoropus androgynus is closely related with Phyllanthus niruri.